PERTUNJUKAN MADIHIN KABUPATEN INDRAGIRI HILIR: KAJIAN SOSIOLOGI SASTRA - Dewi, Gusmina; Syafrial, Syafrial; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study was aimed to describe entertainer, audience, and content (social function) of Madihin Performance in Indragiri Hilir District. This was a descriptive qualitative study. The data collection technique was through an interview and record the Madihin Performance in Indragiri Hilir District. Then, the data which have been collected analyzed using Milles and Huberman theory, known as flow technique, which consists of several stages namely: data collection, data reduction, data presentation, and conclusion. For the entertainer of Madihin, it can be concluded that 1). mostly, the entertainer is old age. This is due to the difficulty of the regeneration process; 2). the entertainer has their basic job. This means that being an entertainer only as an additional job; 3). the entertainer has no position in government, and they are usually uneducated people; 4). there is no standard salary for them. For the audience, it can be classified by their job, tribe, age, and character. Then, for social content, 54 data have found, 23 data serve for entertaining people. It can be classified into 4, namely: 1). offensive to the audience or opponents; 2). entertaining by giving a puzzles; 3). entertaining by asking questions and being answered with the word equation; 4) entertaining with vulgar things; and 31 data serve to entertain by giving something that can be classified into 4, namely: 1) educational function; 2) religion function; 3) social protest function; and 4) advice function.Key words: performance , Madihin, Literature Sosiology